Endoglin interacts with VEGFR2 to promote angiogenesis. Issue 6 (11th January 2018) - Tian, Hongyu; Huang, Jennifer J.; Golzio, Christelle; Gao, Xia; Hector-Greene, Melissa; Katsanis, Nicholas; Blobe, Gerard C.
ABSTRACT: Endoglin, a TGF‐β coreceptor predominantly expressed in endothelial cells, plays an important role in vascular development and tumor‐associated angiogenesis. However, the mechanism by which endoglin regulates angiogenesis, especially during tip cell formation, remains largely unknown. In this study, we report that endoglin promoted VEGF‐induced tip cell formation. Mechanistically, endoglin interacted with VEGF receptor (VEGFR)‐2 in a VEGF‐dependent manner, which sustained VEGFR2 on the cell surface and prevented its degradation. Endoglin mutants deficient in the ability to interact with VEGFR2 failed to sustain VEGFR2 on the cell surface and to promote VEGF‐induced tip cell formation. Further, an endoglin‐targeting monoclonal antibody (mAb), TRC105, cooperated with a VEGF‐A targeting mAb, bevacizumab, to inhibit VEGF signaling and tip cell formation in vitro and to inhibit tumor growth, metastasis, and tumor‐associated angiogenesis in a murine tumor model. This study demonstrate a novel mechanism by which endoglin initiates and regulates VEGF‐driven angiogenesis while providing a rationale for combining anti–VEGF and anti–endoglin therapy in patients with cancer.—Tian H., Huang J. J., Golzio, C., Gao, X., Hector‐Greene, M., Katsanis, N., Blobe G. C. Endoglin interacts with VEGFR2 to promote angiogenesis. FASEB J. 32, 2934–2949 (2018). www.fasebj.org